Synthetic Engineering of Graphene Nanoribbons with Excellent Liquid-Phase Processability - Niu, Wenhui; Liu, Junzhi; Mai, Yiyong; Muellen, Klaus; Feng, Xinliang (Trends in Chemistry, 2019)
Over the past decade, the bottom-up synthesis of structurally defined graphene nanoribbons (GNRs) with various topologies has attracted significant attention due to the extraordinary optical, electronic, and magnetic properties of GNRs, rendering them suitable for a wide range of potential applications (e.g., nanoelectronics, spintronics, photodetectors, and hydrothermal conversion). Remarkable achievements have been made in GNR synthesis with tunable widths, edge structures, and tailor-made functional substitutions. In particular, GNRs with liquid-phase dispersibility have been achieved through the decoration of various functional substituents at the edges, providing opportunities for revealing unknown GNR physiochemical properties. Because of the promise of liquid-phase dispersible GNRs, this mini-review highlights recent advances in their synthetic strategies, physiochemical properties, and potential applications. In particular, deep insights into the advantages and challenges of their syntheses and chemical methodologies are provided to encourage future endeavors and developments.
CRIS-Team Scopus Importer:2023-03-20
Keywords: graphene nanoribbons; liquid phase; organic synthesis; polymer functionalization; processability; supramolecular structure